HUBUNGAN KONDISI LINGKUNGAN DALAM RUMAH DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS PURING KABUPATEN KEBUMEN - Mufidatul Khasanah; Suhartono Suhartono; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Pneumonia is becoming the fifth cause of infant and child mortality, especially in developing countries. Each year as many as 2 million babies pass away because of pneumonia. In 2015, there were  5946 cases (prevalence rate= 50 per 1000 children under five) related to pneumonia occured to the children under five in Kebumen. Puring local clinic ranked the first subdistrict with 501 pneumonia cases to infants. This study aimed to know the association between environmental condition inside the house and pneumonia occurance to children under five in Puring local clinic, Kebumen. This research used observational analytic study with case control design. There were 44 respondents of the treatment group and the same respondent number for the control group.The data were analyzed using univariate and bivariate with chi square test.  The findings of the study showed that there were 5 variables of 11 analyzed independent variables which were related to pneumonia occurance to the children under five; they were ventilation space (p-value=0.009; OR=3.600; 95% CI=1,457-8,893), natural lighting intensity (p-value=0.000; OR=5.686; 95% CI=2,275-14,210), wall type (p-value=0.012; OR=3.750; 95% CI=1,423-9,883), flooring type (p-value=0.015; OR=3,400; 95% CI=1,355-8,531), and cooking  type (p-value=0.003; OR=4.173; 95% CI=1,709-10,188). Hence, it can be concluded that there is a association among the ventilation space, natural lighting intensity, wall type, flooring type, and cooking fuel type with pneumonia occurance to the children under five in Puring local clinic, Kebumen.